The Online Learning Platform Using Animation Media for Storytelling to Enhance Students’ New Normal Learning Outcome - Chatwattana, Pinanta; Onoun, Chutikarn; Wongkhamchan, Janjura (International Journal of Interactive Mobile Technologies (iJIM), 2024)
The online learning platform using animation media for storytelling is a tool designated to be used for public relations, providing students and the general public with helpful and correct educational guidance about curricula and instruction management in the Broadcast Program, College of Industrial Technology, King Mongkut’s University of Technology North Bangkok, Thailand. Thereby, the said platform relies mainly on animation media to give information in the form of storytelling, in which users can interact with the said animation media in real time. The study is based mainly on pre-experimental research, in which the 50 participants, comprising the students of King Mongkut’s University of Technology North Bangkok and the general public, were asked to study with this online learning platform using animation media and then answer the questionnaire in the quality evaluation form with a five-level rating scale. The study results insist that the online learning platform using animation media for storytelling is efficient enough to be used as a tool for public relations and for educational guidance to enhance students’ new normal learning outcome in Thailand. This is because the said platform can provide useful and correct information about the curricula and the instruction management in the broadcast program. In addition, the digital learning environment on this platform is believed to stimulate enthusiasm and interest in learning while promoting access to information through animation media with no limitations of time and place.